Faktor Penentu Pemanfaatan Sertifikat Redistribusi Tanah untuk Mengakses Modal: Studi Kasus Kabupaten Pasaman Barat: Factors that Affect the Use of Land Redistribution Certificates for Accessing Loan: A case study of West Pasaman Regency - Monsaputra; Khursatul Munibah; Dyah Retno Panuju (P4W LPPM IPB, 2022)
West Pasaman Regency has implemented land redistribution to rearrange land tenure, land ownership, land use, and utilization of land. Land redistribution certificates can be used as collateral. The number of redistribution certificates in 2009 until 2018 complemented with mortgage rights was 871 (7,79%). This study aims to determine the factors that affect the use of certificates as collateral for accessing loan. The methods of analysis used was quantitative with surveys and data analysis technique used was logistic regression. The logistic regression resulted several significant factors influencing the use of certificates for collateral including the number of family members, expenditures and land area. Household expenditure and land area had a positive influence, meanwhile the number of family members had a negative effect. Household welfare is an essential factor affecting the likelihood for collateral of land certificates.